2013
DOI: 10.1088/1009-0630/15/1/11
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Effect of N2on Atmospheric-Pressure Cold Plasma CVD of TiO2Photocatalytic Films

Abstract: To deposit TiO2 films through plasma CVD, the partial pressure ratio of O2 to TiCl4 should be greater than the stoichiometric ratio (pO 2 /p TiCl 4 > 1). However, this may lead to the formation of powder instead of film on the substrate when using volume dielectric barrier discharge (volume-DBD) at atmospheric pressure. In this study, by adding N2 into the working gas Ar, TiO2 photocatalytic films were successfully fabricated in the presence of excess O2 (pO 2 /p TiCl 4 = 2.6) by using a wire-to-plate atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…This may be due to the fast gas–liquid plasma preparation process (just 12 min), which is not beneficial to the formation of compact materials. This is consistent with previous work for plasma‐enhanced chemical vapor deposition of TiO 2 films …”
supporting
confidence: 93%
“…This may be due to the fast gas–liquid plasma preparation process (just 12 min), which is not beneficial to the formation of compact materials. This is consistent with previous work for plasma‐enhanced chemical vapor deposition of TiO 2 films …”
supporting
confidence: 93%
“…Due to the relatively mild nature, PECVD has also been used to prepare films on heatsensitive substrates, and to improve film quality. Factors influencing PECVD consist of input power, reactor geometry, and size, negative bias, ion energy, substrate temperature, working pressure, working gas, etc [159].…”
Section: Cold Plasma Deposition Of Catalytic Materialsmentioning
confidence: 99%
“…Each treatment just took 4 min. In our previous work [29] , it was found that the gas temperature estimated in Ar+N 2 was about the same as that in pure Ar gas. In this work, CuO could not be reduced when pure Ar was used as the working gas.…”
Section: Reduction Mechanismmentioning
confidence: 74%